Effect of different decontamination procedures from a saliva-contaminated cured bonding system (Single Bond) - Farideh Darabi; Maryam Tavangar; Reza Davalloo (Wolters Kluwer Medknow Publications, 2012)
Background: A few studies have investigated the effect of saliva contamination of cured or uncured adhesive systems. The aim of this study was to compare the effect of different decontamination methods on the shear bond strength of composite to enamel and dentin using an adhesive contaminated after light activation. Materials and Methods: In this in vitro experimental study, 80 extracted sound human teeth, 40 premolars and 40 central incisors were selected for dentin and enamel specimen preparation. Within each of the two test groups, the teeth were randomly subdivided into five groups. The materials used consisted of single bond (3M) and Z250 (3M). Except group 1 (Control), in Groups 2-5, cured adhesive was contaminated with saliva (20 s). Decontaminating procedures were rinsing, blot-drying, rebonding (Group 2), rinsing, air-drying, rebonding (Group 3), etching, rinsing, blot-drying, rebonding (Group 4) and etching, rinsing, blot-drying (Group 5). Then, composite resin was inserted on the treated surfaces and cured. The results were subjected to one-way ANOVA and Tukey honestly significant difference (HSD) tests. Results: Group 5 (etching, rinsing, blot drying) resulted in significantly lower bond strength to both enamel and dentin surfaces in comparison with the other groups (P < 0.05). Conclusion: When the adhesive was re-applied, all decontamination methods in this study seemed sufficient to decrease the adverse effect of saliva.